Comparing endometriotic lesions with eutopic endometrium: time to shift focus?. Issue 11 (18th September 2021) - Colgrave, Eliza M; Keast, Janet R; Bittinger, Sophie; Healey, Martin; Rogers, Peter A W; Holdsworth-Carson, Sarah J; Girling, Jane E
ABSTRACT: Endometriosis is a heterogeneous disease in terms of patient symptoms, treatment responsiveness and the presentation of endometriotic lesions. This article explores the histological features of endometriotic lesions, highlighting their sometimes underappreciated heterogeneity. We note the variability in evidence for and against the menstrual cycle responsiveness of lesions and consider the utility of drawing parallels between endometriotic lesions and eutopic endometrium. We ask whether histopathologic features beyond just the presence/absence of endometrial-like glands and/or stroma could help improve disease stratification. At the same time, we acknowledge the desire of many clinicians and patients to avoid invasive surgery thereby limiting the ability to histologically phenotype lesions. The ability to derive clinically useful histological information from endometriotic lesions, in association with patient data, would be invaluable to clinicians to help improve treatment options in such a diverse group of patients. However, in suggesting that a shift in focus may enable the development of a better patient stratification system, we recognise that our wish for a single comprehensive stratification system may be beyond reach for a disease of such diverse presentation.